Legal Consequences of Overcollateralization for MSME Customers in Islamic Financing from a Maqashid Sharia Perspective - pingky auliya; Baidhowi Baidhowi (Universitas Negeri Semarang, 2026)
The development of Islamic banking financing in Indonesia plays an important role in supporting the growth of the Micro, Small, and Medium Enterprises (MSMEs) sector. However, in practice, a phenomenon known as overcollateralization often occurs, where the value of collateral required exceeds the amount of financing provided to customers. This condition raises concerns regarding the balance of legal relations between Islamic financial institutions and customers, particularly MSME actors who generally have limited assets and relatively weaker bargaining positions. This study aims to analyze the legal regulation related to the practice of overcollateralization in sharia financing in Indonesia and to examine its legal implications for MSME customers from the perspective of Maqashid Sharia. The research uses a normative legal method with statutory, conceptual, and philosophical approaches, supported by field data obtained through interviews with twelve MSME actors who have received financing from Islamic financial institutions. The findings indicate that regulations concerning collateral in sharia financing have been recognized in the Sharia Banking Law, the Civil Code, and the fatwas issued by the National Sharia Council of the Indonesian Ulema Council. However, these regulations do not specifically regulate the proportionality between the value of collateral and the amount of financing. This situation creates room for overcollateralization practices which, although not explicitly unlawful, may potentially create an imbalance of risk for MSME customers. From the perspective of Maqashid Sharia, such practices may conflict with the objective of protecting wealth (ḥifẓ al-māl). Therefore, stronger regulations and more proportional financing policies are necessary to ensure fairness, balance, and benefit for all parties.